ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN MOBIL TOYOTA FORTUNER DI KOTA PEKANBARU - Lili Sulastri; Sri Restuti Sri Restuti; Marhadi Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aimed to analysze factors that affects on purchase decision, research applied on consumer Toyota Fortuner in Pekanbaru City. The object of this research was consumer who buy Toyota Fortuner in Pekanbaru City. This research consists of ten factors. They are product, price, promotion, distribution after sale, culture factor, social factor, personal factor and psychological factor on purchase decision. This research was conducted using a sample of 117 people. This research used probability sampling, every population have a same chance to be sample in this research. Data are taken by giving respondents structural questionaires. In terms of data analysis, this research used Factor Analysis method using SPSS (Statistical Package for Social Science) version 20. Based on the hypothesis test conducted, research shows that there is three main factors who affects on purchase decision, they are distribution factor, product factor and sosial factor. Distribution factor have the most effect on purchase decision. And distribution factors description based on distribution have more effect on making purchase decision on Toyota Fortuner in Pekanbaru city.Keywords : Analysist factor, Purchase Decision, Distribution Factor.